SKA3 promotes lung adenocarcinoma metastasis through the EGFR–PI3K–Akt axis - Hu, Dan-dan (Biosci Rep, 2020)
The processes that lead to lung adenocarcinoma (LUAD) metastasis are poorly characterized. Spindle and kinetochore associated complex subunit 3 (SKA3) plays a key role in cervical cancer development, but its contribution to LUAD is unknown. Here, we found that SKA3 is overexpressed in LUAD and its expression correlates with lymph node metastasis and poor prognosis. SKA3 silencing experiments identified SKA3 as an oncogene that promotes the metastasis of LUAD cell lines and tissues. SKA3 was found to induce the expression of matrix metalloproteinase (MMP)-2, -7, and -9, which activate PI3K–AKT. SKA3 was also found to bind and activate EGFR to activate PI3K–AKT. In summary, we identify a role for SKA3 in LUAD metastasis through its ability to bind EFGR and activate PI3K–AKT signaling.